Exploring the mechanisms of endophytic bacteria for suppressing early blight disease in tomato (Solanum lycopersicum L.) - Nashwa M. A. Sallam; Heba-Alla S. AbdElfatah; Hadeel M. M. Khalil Bagy; Ameer Elfarash; Kamal A. M. Abo-Elyousr; Kamal A. M. Abo-Elyousr; Edward J. Sikora; Ahmed Sallam; Ahmed Sallam (Frontiers in Microbiology, 2023)
Controlling early blight of tomatoes using endophytic bacteria is an eco-friendly and sustainable approach to manage this common fungal disease caused by Alternaria solani, Alternaria alternata, and Curvularia lunata. Endophytic bacteria are microorganisms that live inside plant tissues without causing harm and can help protect the host plant from pathogens. In this work, twenty endophytic bacterial isolates from tomato healthy plants were tested against pathogenic fungal isolates that caused early blight disease in vitro. Out of the 20 tested isolates, three (B4, B7, and B17) were considered effective isolates against the growth of fungal pathogens. The three isolates were recognized as Enterobacter cloacae HS-6 (B4), Pseudomonas gessardii HS-5 (B 7), and Pseudomonas mediterranea HS-4 (B17) using 16s-rDNA sequencing. Different concentrations of bacterial cultural diltrates at 20, 40, and 60% were tested for their antagonistic effects on the development of pathogenic fungi in vitro. The lowest dry weights of pathogenic isolates in all bacterial culture filtrates were discovered at 60%. In all culture filtrates, phenolic compounds showed the largest peak area. Under greenhouse conditions, the least disease severity of tomato early blight was found for E. cloacae and its culture filtrate compared to other treatments. Real-time PCR was used to examine the expression pattern of the defense response gene β-1.3 glucanase gene in infected tomato plants with pathogenic fungi (control) as well as its relations with efficient biocontrol agent (E. cloacae). The expression of the gene increased substantially and significantly after three days from the inoculation-infected plants with C. lunata and E. cloacae while it reached the maximum after five days from the inoculation with A. alternata, A. solani and E. cloacae. Our study concluded that the endophytic bacterial isolate E. cloacae can be considered a promising biocontrol agent for preventing tomato early blight.